Development of a context-aware game for conducting ubiquitous mathematics learning activities. (1st January 2013) - Huang, Shu-Hsien; Wu, Ting-Ting; Chen, Hong-Ren; Yang, Pei-Chen; Huang, Yueh-Min
The aim of this study is to introduce a context-aware game-based learning interactive method into mathematics instruction. The classroom situation is combined with context-aware ubiquitous learning (u-learning). The situated learning is used to explore differences in learning effects in second grade elementary school students. The mathematics units are addition and subtraction. After class, questionnaires are used to understand student views toward context-aware game instruction. In brief, the results showed that student learning achievement can be enhanced through this situated learning system. In addition, analysis of the questionnaire results demonstrated that the bulk of students gave positive feedback towards the system. Furthermore, the experimental group students were interviewed. Their opinions and views of context-aware game learning showed that most of them felt the instructional method to be helpful to them in regard to learning mathematics.